2018
DOI: 10.1177/1086026618788859
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Organization of Green Activism: Sociological and Economic Perspectives

Abstract: Environmental activists are an important voice in public and private politics, urging governmental and corporate responses and solutions to ongoing environmental damage. Scholars have become increasingly interested in understanding environmental movements and the influence of environmental activist organizations. This article describes two literatures that have analyzed the dynamics and outcomes of activism, one based in a sociological examination of social movements and the other in economic analysis of activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 117 publications
2
10
0
Order By: Relevance
“…We found that a firm’s eco-efficiency is negatively influenced by a relationship with the government but positively influenced by relationships with NGOs. These findings corroborated with the prior conceptualization of the complex influences (e.g., buffering and enabling) of public stakeholders on corporate environmental investment [ 12 , 35 ]; however, they also transcended this conceptualization by demonstrating that each public stakeholder has a specific impact on firms’ pursuit of win–win solutions, as reflected in eco-efficiency.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We found that a firm’s eco-efficiency is negatively influenced by a relationship with the government but positively influenced by relationships with NGOs. These findings corroborated with the prior conceptualization of the complex influences (e.g., buffering and enabling) of public stakeholders on corporate environmental investment [ 12 , 35 ]; however, they also transcended this conceptualization by demonstrating that each public stakeholder has a specific impact on firms’ pursuit of win–win solutions, as reflected in eco-efficiency.…”
Section: Discussionsupporting
confidence: 82%
“…These influencing strategies of stakeholders produce variation in the content of stakeholder salience [ 9 ]. Regarding the two types of public stakeholders on which we focused, prior studies have emphasized the prominent influence of both government and NGOs on a firm’s environmental management [ 12 , 35 ]. The government establishes environmental policies and regulations that govern firms’ environmental investment, while NGOs provide normative incentives for firms’ environmental activities [ 36 ].…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Together with the growing body of research dedicated to this topic, scholars have become better informed about green advocacy (GA) movements and their impact on the policy process (Heyes & King, 2020). In the post-communist world, in which the culture of political participation remains at relatively low levels, GA has its own specifics, making environmental policy one of the most intriguing in the region.…”
Section: Notesmentioning
confidence: 99%
“…But often the most interesting or challenging questions exist at the interstices of disciplines, requiring interdisciplinary collaboration. From this perspective, Heyes and King (2020) offer encouragement that such work is both possible and productive. Organizations like the Alliance for Research on Corporate Sustainability (ARCS), the Group of Research on Organizations and the Natural Environment (GRONEN), and Organizations and the Natural Environment (ONE) offer constructive forums to facilitate such progress.…”
mentioning
confidence: 97%
“…The coherence of the two talks was so striking that I asked the two presenters to coauthor an article bringing together their insights, which they graciously did. The result, “Understanding the Organization of Green Activism: Sociological and Economic Perspectives,” (Heyes & King, 2020) provides a unique overview of current academic understanding and a road map for future interdisciplinary research in this field.…”
mentioning
confidence: 99%